Pemberdayaan Kader Dalam Manajemen Diabetes Dengan Pendampingan Diabetes Self-Management Education Berbasis Keluarga - Wijayanti, Sinta (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
The Sustainable Development Goals target for 2030 is to reduce by 70% the number of deaths from non-communicable diseases, and the highest number of cases is diabetes mellitus, namely 80%. One strategy that can support this program is to carry out Diabetes Self-Management Education to help change lifestyles and improve patients' quality of life. Family and community participation must be formed through integrated service post cadres with family-based diabetes self-management education assistance in Bagelen Village, Gedong Tataan, Pesawaran, Lampung. The activity aims to increase knowledge and behavior of diabetes self-management education by integrated service post cadres. The method used in service activities includes three stages: planning, implementation, and evaluation. The activity results show that assistance in implementing family-based Diabetes Self-Management Education increases Health Cadres' knowledge about self-care management for diabetes patients. Increased knowledge is known from changes in knowledge level scores after service, from poor and sufficient to sufficient and good knowledge.